Determinantes da eficiência técnica da produção de cana-de-açúcar brasileira - Coelho, Luísa Fancelli (Universidade Federal de São Carlos, 2021)
Brazil is currently the world’s largest producer of sugarcane and the importance of this sector has been occurring since the colonial period and has strengthened its relevance in the international market. The increase on the interest of sugarcane reflects an international demand for clean energy and the growing concern with the reduction of greenhouse gases turning Brazil a relevant pole of production. Due to the economic, social and environmental importance that the production of sugarcane and ethanol exert on Brazil, an analysis of the efficiency of these sectors was carried out. The efficiency measure was performed using the data envelopment analysis (DEA). The objective was to calculate the technical efficiency in the production of sugarcane for a sample of municipalities in the states of São Paulo, Goiás, Minas Gerais and Mato Grosso using data from the 2017 Agricultural Census, released by the Brazilian Institute of Geography and Statistics (IBGE, 2017). Additionally, a Tobit model was used to identify the socioeconomical variables affecting sugarcane production efficiencies. There was a concentration of sugarcane production in the mesoregions of Ribeirão Preto and São José do Rio Preto in São Paulo and Triângulo Mineiro/Alto Paranaíba in Minas Gerais. The results pointed that the municipalities with the biggest proportion of rural credit use had higher levels of efficiency in São Paulo. Minas Gerais showed a significant and positive influence regarding to the revenue from sugarcane. The state of Goiás was the only one that showed a positive influence of smallholder farms on efficiencies, while the state of Mato Grosso was the only one that showed positive significance for the average age of the population.
Determinants of technical efficiency from Brazilian sugarcane production
Keywords: Cana-de-açúcar; DEA; Tobit; Sugarcane; DEA; Tobit; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS